Triple-level opportunistic maintenance policy for leasehold service network of multi-location production lines. (October 2019) - Si, Guojin; Xia, Tangbin; Zhu, Ying; Du, Shichang; Xi, Lifeng
Highlights: A triple-level opportunistic maintenance policy is proposed for multi-location production lines. Maintenance costs, lease contracts and geographical locations are comprehensively integrated. Network opportunistic maintenance policy helps to promote the maintenance outsourcing. LNM optimizes global maintenance schemes for the whole leasehold service network. NOM policy significantly reduces maintenance cost for future service-oriented manufacturing. Abstract: The huge investment of multiple devices and the popularization of service-oriented manufacturing have led to increasing requirements for leased production lines. The reliability and maintainability of these leased lines play an important role for an original equipment manufacturer (OEM). For promoting the maintenance outsourcing from a global perspective, this paper presents a triple-level network opportunistic maintenance (NOM) policy for multi-location production lines. At the machine level, sequential predictive maintenance (PM) intervals of every leased machines are dynamically scheduled based on its individual health evolution. At the system level, group PM sets for each multi-unit leased line are obtained by real-time leasing profit optimizations. At the network level, the global maintenance schemes for this leasehold service network are formulated by considering multiple locations of these lines and the maintenance central depot. This comprehensive policy utilizes the triple-level maintenance opportunities to integrate maintenance costs, lease contracts and geographical locations. The mechanism of our proposed policy can ensure the total maintenance cost reduction and significant performance in reliability and robustness for both the lessors and the multi-location manufacturing companies.